Locus of control and human capital investment decisions: The role of effort, parental preferences and financial constraints - Ágnes Szabó-Morvai; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We study the relationship between locus of control (LoC) and human capital investment decisions in the adolescence, using PDS lasso to exploit high-dimensional data. While LoC is not significantly associated with graduation from high school once we use exogenous controls, it correlates strongly with dropout age and college attendance even if we take into account predetermined variables and cognitive abilities, and it exhibits a significant positive relationship with plans to apply to college even if we control for potentially endogenous variables. We find that effort is an important conduit through which LoC operates and it is different from the expectation channel that has been already documented in the literature. The associations are heterogenous: LoC has a significant association with dropout age, high school graduation and college application plans in low-SES families, and with college attendance in mid-SES families. These heterogenous relations are in a large part determined by parental preferences and financial constraints.
Keywords: D91; I21; I23; I24; I26; 330; Human Capital Investment Decision; LoC; Machine learning; PDS Lasso